Microglial colonization routes and their impacts on cellular diversity - Yuki Hattori (Neuroscience Research)
Microglia are the resident immune cells of the central nervous system. Unlike other glial cells—such as astrocytes and oligodendrocytes—which originate from neural stem cells alongside neurons, microglia derive from erythromyeloid progenitors that emerge in the yolk sac during early embryonic development. Once they reach the brain, microglia expand their population through proliferation during development. A growing body of research has revealed that microglia play diverse roles throughout life, both in physiological and pathological contexts. With recent advancements in single-cell transcriptomics, it has become increasingly evident that microglia exhibit substantial heterogeneity in their gene expression patterns. While various functions and subtypes of microglia are being uncovered, the mechanisms underlying their diversity remain largely unknown. Two key hypotheses may explain how microglial diversity arises. One possibility is that their diversity is influenced by the different colonization routes they take before settling in the brain. Alternatively, microglia may acquire distinct properties in response to their local environment. This review explores both possibilities, with a particular focus on the first hypothesis, drawing on recent findings that highlight the multiple routes microglia utilize to colonize the brain. It discusses how these processes contribute to the establishment of microglial diversity during brain development.